The origin and typology of Tombstone in the South-Slavic areas with special reference to the village of Glisnica near Pljevlja - Burhan Čelebić (Historijski pogledi)
Medieval Bosnian tombstone are one of the greatest peculiarities of medieval Bosnia and Herzegovina. During the Ottoman conquests, medieval Bosnian tombstone were still being intensively built among the Bosnian Christians. However, at the moment when Christians became more acquainted with Islam and began to convert to it, the so-called transitional period began. In this period, significant changes occurred in the lives of Christians. As the religious beliefs of the population affected by the Ottoman conquests changed, so did the way gravestones were shaped. This period marks the beginning of different approaches by stone carvers to gravestones. During the transitional period, many places saw the emergence of Muslim cemeteries situated alongside medieval necropolises. Initially, the gravestones were laid horizontally, but soon they also underwent transformation, increasingly being built in the form of pillars with decorations (symbols) borrowed from medieval Bosnian tombstone, such as human figures, animals (eagle, dog, deer, horse, wolf, dragon, snake), weapons (sword, spear, shield, bow and arrow), astral motifs (sun, crescent moon, star), half-apple, hand, arcade, etc. These decorative elements were easily adopted by the new Muslims, who began carving them on their tombstone (Muslim gravestones), showing that the close proximity of medieval Bosnian tombstone had a significant influence on the final design of the tombstone. This led to the situation where the oldest tombstones actually emerged among paternal medieval Bosnian tombstone, i.e, new Muslims expressed a desire to be buried next to their fathers and grandfathers. Such cemeteries with both medieval Bosnian tombstone and tombstones are common in Bosnia and Herzegovina. When we studied this transitional period in the field, we concluded that it is logical to ask whether such examples also exist in Montenegro. Considering the old tombstones from the 15th and 16th centuries located in Tuzima, we found that they resemble those from Bosnia and Herzegovina, with the difference that the tombstone in Tuzima appeared somewhat later compared to the nearly identical tombstones in Bosnia and Herzegovina. When we were alerted to an old cemetery in the village of Glisnica near Pljevlja and visited it, finding medieval Bosnian tombstone among which was a pillar-like tombstone, we realized that this was the same phenomenon present in Bosnia and Herzegovina. We then decided to focus more on researching the mentioned cemetery in Glisnica. The tombstone we discovered in this cemetery is more commonly known as a medieval Bosnian tombstone and an Orthodox grave or Serbian monument, while some authors in specific works consider it a Celtic monument. After all these findings, we decided to present the history, i.e, the affiliation of this tombstone to the usual typology, in this paper, and subsequently explain its ornamentation. At the end of this paper, we have presented our opinion in the conclusion, and through the provided contributions, we have attempted to complete what could not be expressed in words.